Common Endoscopic Findings in Anemic Patients Presenting with Upper Gastrointestinal Bleeding - Devdat, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Upper gastrointestinal (GI) endoscopies frequently have a theoretical indication in elderly patients. Indeed, iron deficiency anemia (IDA) is an indication for GI endoscopies in 5% to 10% of internal medicine inpatients older than 85 years. The prevalence of anemia reaches 25% among geriatric populations, and 20% to 30% of anemia cases are found to be owing to iron deficiency in patients older than 65 years. Weight loss and isolated GI symptoms are additional indications for GI endoscopy. The present study was conducted to determine the endoscopic findings in anemic patients with upper GI hemorrhage presenting to district general Hospital Materials & Methods: Our study was conducted in Gastroenterology department, district general Hospital as a descriptive cross sectional study since 10th January 2021 to 31st March 2022. Results: Out of total 300 patients with upper GI hemorrhage and resulting anemia included in this study, there were 184 male and 116 female patients with a male to female ratio of 1.7:1, and mean age of 48.09±15.71 years. The most common cause of upper GI hemorrhage was found to be esophageal varices (55.5%) followed by peptic ulcer (36.6%), gastric erosions (5.8%), Mallory-Weiss tear (1.3%) and esophagitis (0.5%). Conclusion: Variceal bleeding is the most common endoscopic finding in the patients with UGIB. Other lesser common causes include erosions of the gastric and esophageal mucosa. Keywords: Gastrointestinal Hemorrhage; Endoscopy, Gastrointestinal; Esophageal & Gastric Varices; Peptic Ulcer; Esophagitis, Peptic.